Intravenous Morphine vs Intravenous Ketofol for Treating Renal Colic; a Randomized Controlled Trial - Faridaalaee, Gholamreza; Mohammadi, Neda; Merghati, Seyedeh Zahra; Keyghobadi Khajeh, Fatemeh; Naghipour, Bahman; Pouraghaei, Mahboob; Ahmadi, Sajjad (Archives of Academic Emergency Medicine, 2018)
Introduction:Â The main purpose of emergency department (ED) management for renal colic Â is prompt pain relief. The present study aimed to compare the analgesic effects of intravenus (IV) ketofol with morphine in management of ketorolac persistent renal colic.Â Methods: This study is a single blind randomized, clinical trial, on patients who were presented to ED with renal colic, whose pain was resistant to 30 mg IV ketorolac. The patients were randomly assigned to either IV morphine (0.1 mg/kg) or IV ketofol (0.75 mg/kg propofol and 0.75 mg/kg) and the measures of treatment efficacy were compared between the groups after 5 and 10 minutes.Â Results:Â 90 patients with mean age of 38.01 Â± 9.78 years were randomly divided into 2 groups of 45 (66.7% male). Treatment failure rate was significantly lower in ketofol group after 5 (20% vs 62.2%, p < 0.001) and 10 minutes (11.1% vs 44.4%, p < 0.001). ARR and NNT for ketofol after 5 miutes were 42.22% (95% CI: 23.86 â€“ 60.59) and 3 (95% CI: 1.7 - 4.2), respectively. After 10 minutes, these measures reached 33.33 (95% CI:16.16 â€“ 50.51) and 4 (95% CI: 2.0 - 6.2), respectively. NNH and ARI for hallucination or agitation were 12 (95%CI: 5.8 - 174.2) and 8.89% (0.57 - 17.20), respectively.Â Conclusion:Â The results of the present study, showed the significant superiority of ketofol (NNT at 5 minute = 3 and NNT at 10 minute = 4)Â in ketorolac resistant renal colic pain management. However, its NNH of 12, could limit its routine application in ED for this purpose.